MUSCARINIC RECEPTOR SUBTYPES OF GUINEA-PIG COMMON BILE-DUCT - (:unkn) unknown (ARCH INT PHARMACODYNAMIE, 1991)
The antagonism of carbachol-induced contractions of guinea-pig common bile duct smooth muscle strips by various antagonists has been investigated in order to find out the muscarinic receptor subtype(s) of common bile duct smooth muscle. Atropine, pirenzepine, 4-DAMP and AF-DX 116 were used as nonselective, M1-selective, M1- and M3-selective and M2-selective muscarinic antagonists, respectively. All muscarinic antagonists examined displaced the concentration-response curves to the right, parallelly and in a concentration-dependent manner, without affecting maximum response. Schild analysis of data was consistent with competitive antagonism. pA2 values of the antagonists were as follows: atropine, 9.59; pirenzepine, 7.32; 4-DAMP, 8.99; AF-DX 116, 6.85. When these pA2 values are compared with those obtained in the ileum, it may be concluded that the muscarinic receptors of the guinea-pig common bile duct mediating cholinomimetic-induced contractions, are of the M3 subtype, but not of the M1 and M2 subtypes.
Keywords: IDENTIFICATION; AFFINITY; MUSCLE; CELLS; ILEUM